Characteristics of non-melanoma skin cancer depending upon occupational solar UV exposure dosage - Alexandra-Irina Butacu; Marc Wittlich; Swen Malte John; Sabina Zurac; Horatiu Moldovan; George-Sorin Tiplica (Romanian Medical Journal, 2020)
Objectives. Non-melanoma skin cancer (NMSC) is the most common human malignancy and is strongly related to solar ultraviolet (UV) radiation exposure. Occupational UV exposure is associated with a two-fold increased risk of developing NMSC, but still only few European countries recognize NMSC as an occupational disease. The study aims to analyze the clinical and histopathological features of NMSC with regard to personal cumulative occupational UV exposure doses. Material and methods. A retrospective, analytical, comparative study was conducted during 2017-2019 with focus on outdoor workers presenting with NMSC. Occupational solar UV exposure dose was calculated based on the Wittlich algorithm and cumulative lifetime exposure of the general population of the same age was estimated according to German Standards of 130 SED/year. Subjects were divided in two groups (OW1 and OW2) according to differences between occupational exposure and estimated cumulative lifetime exposure of the general population. High-risk clinical and histopathological characteristics were compared between groups. Outcomes. The study included 25 consecutive outdoor workers diagnosed with BCC (N=21) and SCC (N=4). Occupational solar UV exposure doses were calculated for Romanian workers and identified mean values of 17695 SED two times higher than estimative leisure cumulative lifetime solar UV exposure for a person of the same age from the general population according to German standards of 130 SED/year. Subjects were classified in two groups: group 1 (OW1) included subjects who were exposed to an additional occupational UV dose less than 50% of the cumulative lifetime exposure dose of a person of the same age from the general population according to German standards and group 2 (OW2) included subjects exposed to additional professional UV doses higher than 50%. 12 subjects were included in OW 1 and 13 subjects in OW2. Data analysis between groups identified significant statistical differences with regard to high-risk body locations and tumour size, present in 100% of OW2 and 58.3% of OW1 (χ2 (1, N=51) = 6.771, p=0.015) and to high-risk histopathological subtypes, present in 56% OW2 and 33.3% OW1 (χ2 (1, N=51) = 4.812, p=0.036). Ulceration was present on the histopathological report of all subjects in OW2. OW2 was associated with higher percentages of moderate to severe grades of actinic elastosis and of desmoplastic reaction and a more rapid evolution of lesions. Conclusions: Outdoor workers in Romania are exposed to an occupational solar UV dose two times higher than the cumulative lifetime exposure dose of the general population of the same age which may receive up to 130 SED/year according to German standards and they bear an increased risk of NMSC. Occupational NMSC induced by UV exposure should be recognized as an occupational disease if the subject received more than 50% additional UV exposure at the workplace.